Surfactant flooding in oil-wet micromodels with high permeability fractures. (1st April 2019) - Mejia, Lucas; Tagavifar, Mohsen; Xu, Ke; Mejia, Miguel; Du, Yujing; Balhoff, Matthew
Highlights: Low IFT was the main oil recovery mechanism for gravity driven imbibition. With negligible gravity, solubilized oil diffused out of micromodel in a month. Wettability alteration was not clearly identified as a mechanism for oil recovery. Transverse viscous pressure gradients recovered oil in displacement experiments. Abstract: Recovery in carbonate reservoirs is challenging because they are often oil wet and highly fractured. Surfactant flooding has been proposed as a possible enhanced oil recovery method to address these problems. To better understand the mechanisms of oil recovery from oil-wet, fractured rocks using surfactants, we created oil-wet glass micromodels, traversed by a deep fracture (130 µm) and conducted surfactant spontaneous imbibition experiments and floods at typical reservoir flow rates (approximately 2 ft/day). We compared the effects of capillary, viscous, and gravity forces as well as wettability alteration. We show, by conducting spontaneous imbibition experiments with negligible gravity effects (inverse Bond number ∼10 5 ) and by analyzing the results using simple force balance calculations, that in our micromodels low IFT plays the key role in balancing the viscous, gravity, and surface forces and hence the dynamics of imbibition. To quantify the role of viscous forces, we present displacement experiments at low IFT (10 −3 mN/m) where transverse viscous pressure gradients mobilize oil from the matrix into the fracture. These results help rationalize and quantify the contributions of gravity, wettability alteration, and viscous crossflow to the rate of matrix-fracture transfer at low-IFT conditions.